The Effect of Variation of Genital Appearance in Thai WomenSingle-Dose Antenatal Dexamethasone in Reducing Respiratory Complications in Late Preterm - Tansita Chinkangsadan; Purim Ruanphoo; Suvit Bunyavejchevin (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To study the normal variation of Thai female genitalia and the difference in premenopausal and postmenopausal age groups.Materials and Methods: One hundred and fifty five Thai women having the annual pelvic examination at King Chulalongkorn Memorials Hospital from May 2017 to April 2018 were recruited. The inclusion criteria were: age between 20-70 years, satisfied with the external genitalia as classified by Thai version of Genital Appearance Satisfaction questionnaires and not seeking for genital cosmetic surgery. The height, weight, body mass index, parity, route of prior delivery, contraception method, age at menopause, and the used of postmenopausal hormonal therapy were recorded. The genital appearance measurements included 10 parameters (length of clitoris, clitorial gland width, clitoro-urethral length, labia minora length and width, labia majora length, perineal length, protusion of labia minora, and the appearance of the perineum).Results: The median (interquartile range) of left and right labia minora width were 10.46 (6.61, 14.12) and 9.69 (6.25, 14.62) mm. Most women had the darker color of the perineum than the skin of inner thigh (47.7%). Forty four women (28.4%) reported of having ridge at the labia majora. When comparing the genital appearances in premenopausal and postmenopausal group, the clitorial length, clitoro-urethral length and labia minora length were statistically different (p < 0.001).Conclusion: We found the wide range of the variation of female genital appearances in Thai women who were satisfied with their own genital appearance. This information would be useful for the preoperative counseling for Thai women who are not satisfied with her own appearance and seek the genital cosmetic surgery without medical indication to avoid the regret after surgery.